DI-061 Adherence to treatment with the new strategies in patients with chronic hepatitis c. (14th February 2016) - Gonzalez-Colominas, E; Echeverría-Esnal, D; Retamero, A; De Antonio, M; García, R; Carballo, N; Luque, S; Conde-Estevez, D; Ferrandez, O; Salas-Sanchez, E
Abstract : Background: Interferon free treatments (IFT) for chronic hepatitis C (CHC) consist of more feasible and better tolerated regimens that could help to improve adherence. Nevertheless, little is known about adherence to these treatments in clinical practice. Purpose: To evaluate adherence to IFT in clinical practice and non-adherence risk factors. Material and methods: Patients completing IFT for CHC in a tertiary hospital were included (December 2014 to September 2015). Baseline characteristics including concomitant medications were recorded. Adherence was calculated as a percentage from pill count records performed in each drug dispensing visit (every 4 weeks) and at the end of treatment. Ribavirin dose reductions were not considered as lack of adherence. Bivariate analysis of baseline characteristics in patients with and without 100% adherence was performed. Fisher's test and the Mann-Whitney U test were used for categorical and continuous variables, respectively. Results: 78 patients were included: median age was 59 years, 55 (70.5%) were male, 48 (61.5%) with genotype 1b, 15 (19.2%) with HIV coinfection, 53 (67.9%) with cirrhosis and 36 (46.2%) were naïve. Mean number of concomitant drugs was 3.31 (SD 2.7). 69 (88.5%) patients received 12 weeks of treatment. No differences were found in demographics, genotype, HIV coinfection, previous antiviral treatment or number of concomitant medications between patients with and without 100% adherence. Conclusion: Observed adherence rates to all IFT in clinical practice were superior to 90%. None of the analysed factors seemed to influence patient adherence, probably due to the low number of patients and the excellent rates of adherence observed. References and/or Acknowledgements: Pawlotsky JM. EASL Recommendations on Treatment of Hepatitis C 2015. J Hepatol 2015 No conflict of interest.